AI-Resistant Assignments in Writing Class: Insights from Australian Higher Education Websites - Wardhani, Brigitta Dia Putri Kusuma (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
The usage of Artificial Intelligence (AI) tools such ChatGPT and Gemini in higher education is increasing worldwide, especially for writing assignments. A growing number of students use AI to develop and finding ideas for the topic or main theme, create outlines, and complete tasks, raising significant concerns about academic integrity. This study investigates strategies for designing AI resistant writing assignments in English as a Foreign Language or namely EFL classrooms. A Systematic Literature Review method (SLR method) was conducted, analyzing twenty webpages from nine Australian universities (2020–2025) identified through targeted Google searches and institutional relevance criteria. The analysis identifies four primary strategies: redesigning assignments, regulating AI use, strengthening integrity policies, and fostering dialogue between lecturers and students. Recommended practical solutions include process based writing, reflective journals, and supervised assessments. The findings offer insights for developing resilient writing practices and inform future research on AI resistant pedagogy